A Rare Case of Pituitary Carcinoma With Bone Metastases: 68Ga-DOTATATE PET/CT Findings. (13th March 2022) - Filizoglu, Nuh; Ozguven, Salih
Abstract: Pituitary carcinomas are extremely rare and aggressive tumors that comprise only 0.2% of all pituitary tumors. Because of its rarity, pituitary carcinomas are difficult to diagnose. Conventional imaging methods are inadequate to detect metastatic lesions. Pituitary carcinomas are neuroendocrine tumors and express somatostatin receptors; therefore, 68 Ga-DOTATATE PET/CT may be used in the staging of these rare tumors. Herein, we present an exceptional case of pituitary carcinoma with sclerotic skeletal metastases showing 68 Ga-DOTATATE uptake.